Neuronal Mechanism for Compensation of Longitudinal Chromatic Aberration-Derived Algorithm - Barkan, Yuval; Spitzer, Hedva (Frontiers in Bioengineering and Biotechnology, 2018)
The human visual system faces many challenges, among them the need to overcome the imperfections of its optics, which degrade the retinal image. One of the most dominant limitations is longitudinal chromatic aberration (LCA), which causes short-wavelengths (blue light) to be focused in front of the retina with consequent blurring of the retinal chromatic image. The perceived visual appearance however, does not display such chromatic distortions. The intriguing question, therefore, is how the perceived visual appearance of a sharp and clear chromatic image is achieved despite the imperfections of the ocular optics. To address this issue, we propose a neural mechanism and computational model, based on the unique properties of the s-cone pathway. The model suggests that the visual system overcomes LCA through two known properties of the S-channel: a) Omitting the contribution of the S-channel from the high spatial resolution pathway (utilizing only the L and M channels). b) Having large and coextensive receptive fields that correspond to the small bistratified cells. Here we use computational simulations of our model on real images to show how integrating these two basic principles can provide a significant compensation for LCA. Further support for the proposed neuronal mechanism is given by the ability of the model to predict an enigmatic visual phenomenon of large color shifts as part of the assimilation effect.